2003
DOI: 10.1007/s00221-003-1388-6
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate and AMPA receptor immunoreactivity in Ia synapses with motoneurons and neurons of the central cervical nucleus

Abstract: Axonal tracing and high resolution immunocytochemistry were used to identify transmitter content and postsynaptic receptors in synapses between Ia primary afferents and motoneurons and in neurons of the central cervical nucleus (CCN), respectively, in the rat. The terminals, as well as the target neurons, were identified by postembedding immunogold detection of transganglionically or retrogradely, respectively, transported cholera toxin B subunit (CTB), and in adjacent sections postembedding immunogold was emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…There is now abundant evidence that VGLUT1 is present in large diameter low threshold skin and muscle primary afferent terminals in the spinal cord, corroborating extensive electrophysiological/pharmacological and glutamate immunogold labeling data supporting a transmitter role of glutamate in such terminals (e.g. Salt and Hill, 1983;Jahr and Yoshioka, 1986;Schouenborg and Sjölund, 1986;Gerber and Randic, 1989;Walmsley and Nicol, 1991;Maxwell et al, 1990a;Broman et al, 1993;Maxwell et al, 1993;Broman and Ådahl, 1994;Valtschanoff et al, 1994;Örnung et al, 1995;Larsson et al, 2001;Ragnarson et al, 2003). Dorsal rhizotomy results in significant depletion of large VGLUT1 immunolabeled varicosities in the ventral horn and deep dorsal horn (Li et al, 2003;Oliveira et al, 2003;Alvarez et al, 2004;Wu et al, 2004), and essentially all primary afferent terminals in these VGLUT1 and VGLUT2 co-localize in a proportion of varicosities in laminae III-IV and lamina IX, further support the notion that some primary afferent terminals in both the deep dorsal horn and the ventral horn express VGLUT2 in addition to VGLUT1.…”
Section: Origin Of Immunolabeled Terminalsmentioning
confidence: 77%
“…There is now abundant evidence that VGLUT1 is present in large diameter low threshold skin and muscle primary afferent terminals in the spinal cord, corroborating extensive electrophysiological/pharmacological and glutamate immunogold labeling data supporting a transmitter role of glutamate in such terminals (e.g. Salt and Hill, 1983;Jahr and Yoshioka, 1986;Schouenborg and Sjölund, 1986;Gerber and Randic, 1989;Walmsley and Nicol, 1991;Maxwell et al, 1990a;Broman et al, 1993;Maxwell et al, 1993;Broman and Ådahl, 1994;Valtschanoff et al, 1994;Örnung et al, 1995;Larsson et al, 2001;Ragnarson et al, 2003). Dorsal rhizotomy results in significant depletion of large VGLUT1 immunolabeled varicosities in the ventral horn and deep dorsal horn (Li et al, 2003;Oliveira et al, 2003;Alvarez et al, 2004;Wu et al, 2004), and essentially all primary afferent terminals in these VGLUT1 and VGLUT2 co-localize in a proportion of varicosities in laminae III-IV and lamina IX, further support the notion that some primary afferent terminals in both the deep dorsal horn and the ventral horn express VGLUT2 in addition to VGLUT1.…”
Section: Origin Of Immunolabeled Terminalsmentioning
confidence: 77%
“…Popratiloff et al, 1996S. A. Popratiloff et al, 1998;Ragnarson et al, 2003), the pattern of AMPA and NMDA receptor expression at individual synapses remains largely elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Although conventional immunocytochemical studies have been performed to detect AMPA subunits (Tachibana et al, 1994;Jakowec et al, 1995a;Popratiloff et al, 1996Popratiloff et al, , 1998Morrison et al, 1998;Spike et al, 1998), it is unlikely that these revealed receptors at glutamatergic synapses, because these are thought to be inaccessible due to extensive cross-linking of the protein meshwork of the synaptic cleft and postsynaptic density that results from aldehyde fixation (Baude et al, 1995;Ottersen and Landsend, 1997;Fritschy et al, 1998;Watanabe et al, 1998). Postembedding immunogold-labeling has been used to investigate synaptic AMPA receptors in the spinal cord (Popratiloff et al, 1996(Popratiloff et al, , 1998Morrison et al, 1998;Ragnarson et al, 2003); however, despite this, the pattern of AMPA subunit expression at individual synapses remains largely elusive.…”
Section: Introductionmentioning
confidence: 99%